Glycolipid Sensing and Innate Immunity in Paracoccidioidomycosis - Batista, Vanessa G.; Toledo, Marcos S.; Straus, Anita H.; Mendes-Giannini, Maria José Soares [UNESP]; Duarte, Alberto J. S.; Takahashi, Helio K.; Benard, Gil (Springer, 2014)
Distinct glycolipid profiles are described in microorganisms, which have been shown to modulate the innate immune system. We tested the hypothesis that glycosphingolipids from Paracoccidioides brasiliensis have immunomodulatory properties on monocytes and dendritic cells of two groups of healthy individuals, one cured of paracoccidioidomycosis in the past (CUR-I) and the other nonexposed to P. brasiliensis (HNE-I). Two classes of glycosphingolipids purified from yeast cells were evaluated: a neutral glycosphingolipid, monohexosylceramide (CMH), and acidic glycosylinositolphosphorylceramides (GIPCs). Both glycosphingolipids affected the functioning of innate immunity cells, interfering with the antigen presenting process: P. brasiliensis yeast cells phagocytosis, IL-10 secretion, and costimulatory molecules and recognition receptors expression by monocytes were altered, while dendritic cell antigen presentation to autologous T cells was markedly down-modulated as shown by reduced T-cell proliferative responses. The mechanisms by which CMH and GIPCs exert their effects differ since the target cells did not always respond similarly to the challenge with the glycosphingolipids. Moreover, CUR-I and HNE-I presented different responses to the glycosphingolipids. Differences not only in the glycosphingolipid structure (such as the polar head group or the ceramide moiety), but also in the innate immunity properties of CUR-I and HNE-I, may underlie these differences and contribute to individual's susceptibility or resistance to develop paracoccidioidomycosis.
Keywords: Paracoccidioidomycosis; Glycolipids; Innate immunity; Glycosphingolipids